SERVICE QUALITY MEASURE IN ETHIOPIAN HIGHER EDUCATION CONTEXT: DEVELOPING A COMPREHENSIVE MEASURE - Oliso, Zelalem (RADJA PUBLIKA, 2023)
The main purpose of this study was conducted to develop a comprehensive Higher Education Service Quality Measure [HESQM] that used to evaluate Ethiopian higher education service quality. To serve this purpose, the existing generic service quality models and models designed for higher education sectors were thoroughly reviewed. Through an extensive review, a comprehensive HESQM was developed. The content validity and reliability of the instrument was checked. The content validation of the instrument was judged by five experienced experts who selected from Arba Minch University. The experts’ judgment in each item was quantitatively calculated using Item-Level Content Validity Index [I-CVI] and Scale-Level Content Validity Index [S-CVI]. The pilot study was conducted on twenty Graduating Class [GC] students who purposefully selected from the different departments of Arba Minch University to further analyze the reliability of the instrument. The internal consistency of the instrument was checked via Cronbach’s alpha coefficient 0.5 using SPSS v.20. Both content validation and reliability analysis results confirm that the instrument was valid and internally consistent. The new comprehensive HESQM has seven main and nine sub dimensions and included a total of 118 items. The present HESQM is a comprehensive model to measure Ethiopian higher education service quality. Since using a single model unable to fully explain the Ethiopian higher education service quality, the new comprehensive model has better explaining Ethiopian higher education service quality. However, further studies should be conducted using Exploratory Factory Analysis [EFA] to strengthen the present findings.